UJI EFEK ANTIINFLAMASI FRAKSI KLOROFORM DAUN JOHAR (Cassia siamea Lamk.) DENGAN METODE RAT HIND PAW EDEMA - Sitti Amirah; Hendra Herman (Fakultas Farmasi UMI, 2015)
Johar (Cassia siamea Lamk.) leaves widely used as a traditional medicine. Johar leaves contain chemical compounds such us alkaloids, tannins, saponins, flavonoids, sitosterol and barakol which have effect of treatment for several diseases including inflammatory. This study aims to determine anti-inflammatory effect of chloroform fraction C.siamea leaves. This study was conducted using 15 Wistar rats were divided into 5 groups: control group who were given suspension of Na.CMC 1% w / v, the comparison group were given diclofenac sodium suspension 0.35 mg / kg, the test group dose of 75 mg / kg, the test group dose of 150 mg / kg and a test group of 300 mg / kg. Evaluation of anti-inflammatory activity was done by measured initial volume of the foot all test animal then given the drug orally according to dosage of its group. After 30 minutes, each group made inflammatory by induced karagen 1% 0.1 mL by intraplatar. Furthermore, inflammation’s degrees was measured every hour for 8 hours. The results obtained show that after 2 hours, inflammatory of the control group Na.CMC had increased much higher compared to the other groups. This is shows that Na.CMC doesn’t have effects anti-inflammation. The comparison group diclofenac sodium gave the best inhibitory effect that have been shown from an increase volume of feet smaller than the test group chloroform fraction of Johar leaves. While in chloroform fraction of Johar leaves test group, group with dosage 75 mg/kg gave an inhibitory effect better than the other test group dosage.